2022
DOI: 10.1093/femsec/fiac114
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles released byBeauveria bassianainduce oviposition behavior in the fall armywormSpodoptera frugiperda(Lepidoptera: Noctuidae)

Abstract: Microbial volatile organic compounds may act as semiochemicals, inciting different behavioral responses in insects. Beauveria bassiana is an entomopathogenic fungus, and physiological and environmental factors are positively related to fungal virulence. In this study, we examined the volatile profiles produced by eight B. bassiana strains, isolated from soil plots and mycosed insect cadavers, with different speeds of kill and determined if these compounds induce oviposition behavior in Spodoptera frugiperda. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…In contrast, Liu et al (2003) found a positive correlation between conidial length and virulence of B. bassiana isolates. Additionally, a recent study (Ramírez-Ordorica et al 2022) demonstrated a different chemical signature and higher virulence of B. bassiana isolates from mycosed insect cadavers than those obtained from soil.…”
Section: Molecular Identification Of Beauveria Bassiana Isolatesmentioning
confidence: 99%
“…In contrast, Liu et al (2003) found a positive correlation between conidial length and virulence of B. bassiana isolates. Additionally, a recent study (Ramírez-Ordorica et al 2022) demonstrated a different chemical signature and higher virulence of B. bassiana isolates from mycosed insect cadavers than those obtained from soil.…”
Section: Molecular Identification Of Beauveria Bassiana Isolatesmentioning
confidence: 99%
“…Trichoderma is an endophytic fungus commonly found on leaf tissue, roots, and sapwood and provides several advantages to its host (Cummings et al, 2016). This genus also plays a crucial role in protection against herbivorous arthropods, and critical functions for fungal metabolites in herbivory have also been described (Ramıŕez-Ordorica et al, 2022). Recently, (Contreras-Cornejo et al, 2018a) investigated how T. atroviride affected the ability of maize (Zea mays) to resist the insect herbivore Spodoptera frugiperda.…”
Section: Trichoderma Applications In the Agricultural Sectormentioning
confidence: 99%
“…It was also observed that the production of antibiotics or siderophores from several Trichoderma secondary metabolites plays a vital role in controlling plant growth and development, as well influencing the growth of plant pathogenic microorganisms in the soil ( Contreras-Cornejo et al., 2014 ; Contreras-Cornejo et al., 2020 ). Moreover, ( Ramírez-Ordorica et al., 2022 ) revealed that an entomopathogen might have an ecological benefit in that it can accelerate the expansion of the insect population if it can create volatiles that provides olfactory stimulation of egg-laying activity.…”
Section: Trichoderma Applications In the Agricultural Sectormentioning
confidence: 99%
“…In the olive fly, Bactrocera oleae, electrophysiological studies demonstrated that antennal sensilla responded to Pseudomonas putida bacterial filtrate odor, methyl thioacetate, olive leaf and olive, while acetic acid produced an inhibitory response in single sensillum recording [54]. Similarly, a study has shown that bacterial metabolites also influence the egg-laying behavior of insects via their influences on olfactory recognition [55]. A study in the primary screwworm, Cochliomyia hominivorax, has shown that it prefers to oviposit on blood that has been inoculated by certain bacteria due to the volatile compounds released by these bacteria [56].…”
Section: Effects Of Bacterial Volatiles On Insect Behaviors Through O...mentioning
confidence: 99%